2017
DOI: 10.1111/jpc.13752
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods to estimate glomerular filtration rate in paediatric oncology patients

Abstract: A number of equations were identified that could be used to estimate renal function in paediatric oncology patients; however, none was found to be highly accurate. The Flanders metadata equation and univariate Schwartz performed the best in this study, and we would suggest that these two equations may be used cautiously in paediatric oncology patients for clinical decision making, understanding their limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
(120 reference statements)
4
16
0
Order By: Relevance
“…Such worse performance was somewhat expected because malignancies and inflammation increase the serum levels of B2MG 10 that is probably reason for B2MG-based eGFR equations being the only iGFR-underestimating ones. It should be also noted that eGFR equations specifically developed based on children having malignancies (Brandt, Millisor, Cole weight , Cole Cr ) were not among the best performing equations, similarly to a recent study 7 . The reason for their poor performance could be small dataset 25 , use of iothalamate that exhibits significant tubular secretion 13 for development of the equation 24 or exclusion of often incorporated covariates, such as age and sex, from the equation 23 , in contrast to Lund-Malmo revised and Gao equations 21,22 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Such worse performance was somewhat expected because malignancies and inflammation increase the serum levels of B2MG 10 that is probably reason for B2MG-based eGFR equations being the only iGFR-underestimating ones. It should be also noted that eGFR equations specifically developed based on children having malignancies (Brandt, Millisor, Cole weight , Cole Cr ) were not among the best performing equations, similarly to a recent study 7 . The reason for their poor performance could be small dataset 25 , use of iothalamate that exhibits significant tubular secretion 13 for development of the equation 24 or exclusion of often incorporated covariates, such as age and sex, from the equation 23 , in contrast to Lund-Malmo revised and Gao equations 21,22 .…”
Section: Discussionsupporting
confidence: 64%
“…This seemingly contrasts with other studies in children with malignancies that have shown better performance of cystatin C-based or combined (creatinine-and cystatin C-based) compared with solely creatinine-based eG-FR equations 2,9 . However, to the best of our knowledge, previous studies in children with malignancies have not evaluated Lund-Malmö revised equation and Gao equation has been studied only once 7 . In a validation study in children with cancer 7 , Gao equation was the worst performing equation, but the study included younger children with lower renal function than in the equation development dataset on whom Gao equation performed the worse 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystatin C is eliminated mainly by glomerular filtration, correlates with GFR, and it is very sensitive even in mildly impaired kidney function so some studies have suggested it as an ideal GFR marker in pediatric oncology (36) . The validation of the Schwartz formula and the calculations based on serum CysC was done in several studies by comparing them to nuclear scanning methods, which suggest that they are closely correlated to GFR (37)(38)(39) . In our study, we found the strongest correlation between the CysC -GFR and the Schwartz-GFR calculations, and comparison of CrCl and eGFRs revealed positive linear regression lines, which may be used as alternatives to creatinine-based estimations in CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the prevalence of glomerular hyperfiltration requires correct measurement of GFR, but the predictive performance of commonly used creatinine‐based equations for calculating estimated GFR (eGFR) performs poorly in children with cancer 2,3,9 . Use of biomarkers like cystatin C 10,11 and β 2 ‐microglobulin 12,13 is possible alternative for estimating GFR, but these may introduce bias because inflammation increases the concentration of both markers, 10,12 although in case of cystatin C this association is controversial, 14 and β 2 ‐microglobulin is further elevated due to malignancies 12 …”
Section: Introductionmentioning
confidence: 99%